Musical activity for multi-touch system to promote user interaction - Yang, LiJia (2013)
With technology improving each day, there is an increasing amount of multi touch devices in the market. However, such devices are mostly designed for a single user. Even in multi-player games, the direct interaction between users is minimal as users would only focus and interact with the graphical screen.